The impact of nutritional labels and socioeconomic status on energy intake. An experimental field study - Crockett, Rachel A.; Jebb, Susan A.; Hankins, Matthew; Marteau, Theresa M. (Appetite, 2014)
•The impact on consumption of low fat and high fat labels was explored.•There were no main effects across a general population sample.•There were three-way interactions of socioeconomic status, label and weight concern.•Effects of nutritional labelling vary across different population subgroups. There is some evidence for paradoxical effects of nutritional labelling on energy intake particularly amongst restrained eaters and those with a higher body mass index (BMI) resulting in greater consumption of energy from foods with a positive health message (e.g. “low-fat”) compared with the same foods, unlabelled. This study aimed to investigate, in a UK general population sample, the likelihood of paradoxical effects of nutritional labelling on energy intake. Participants (n = 287) attended a London cinema and were offered a large tub of salted or toffee popcorn. Participants were randomised to receive their selected flavour with one of three labels: a green low-fat label, a red high-fat label or no label. Participants watched two film clips while completing measures of demographic characteristics, emotional state and taste of the popcorn. Following the experiment, popcorn consumption was measured. There were no main effects of nutritional labelling on consumption. Contrary to predictions neither BMI nor weight concern moderated the effect of label on consumption. There was a three-way interaction between low-fat label, weight concern and socioeconomic status (SES) such that weight-concerned participants of higher SES who saw a low-fat label consumed more than weight unconcerned participants of similar SES (t = −2.7, P = .04). By contrast, weight-concerned participants of lower SES seeing either type of label, consumed less than those seeing no label (t = −2.04, P = .04). Nutritional labelling may have different effects in different socioeconomic groups. Further studies are required to understand fully the possible contribution of food labelling to health inequalities.